THE PROBLEM OF THE TECHNOLOGY OF CREATING THE IMAGE OF THE LEADER OF THE EDUCATIONAL INSTITUTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article reveals the psychological and pedagogical aspect of the formation of the image in the professional activity of the head of an educational institution, a teacher. The structure of the professional image and the principles of its construction are considered.The article presents the main idea of the science of imageology - as a special science of the man, whose main goal is an individual self-realization. The article presents the analysis and the modern concept of terms as “image”, “professional image”, "Image of the head of an educational institution" , “image of a teacher”.